Long-Term Ultrasonographic Changes of the Testicle in Patients with a History of Orchiopexy after Testicular De-torsion, a Cross-sectional Prospective Study: Ultrasonographic Changes after Orchiopexy in Children - Jazebi, Samineh; shojaeian, Reza; Ameri, Leila; Parvizi Mashhadi, Mahdi (Iranian Journal of Pediatric Surgery, 2024)
Introduction: Testicular torsion (TT) necessitates emergent and proper intervention since it can affect sexual health and fertility. Ultrasonography is the gold standard modality for detecting TT. This study aimed to determine the long-term sonographic changes of the testicles in patients with a history of orchiopexy for testicular torsion in the pre-and post-operative stages who were referred to our tertiary pediatric referral emergency department in 2017-2018, northeast of Iran. Methods: In this analytical cross-sectional study, we have collected patients referred to the urology department with acute scrotum complaints and followed up clinically and sonographically on the size of their testicles. Results: The left testicle was found to be torsified in 24 (72.7%) cases. In the control ultrasound, 12 (38.7%) cases of involvement of the left side of the testicle were reduced in size. In the post-operative stage, the percentage of involvement in the right testicle (0.87%) was higher than in the left (0.50%). The percentage of parenchymal involvement frequency before and after the operation was compared using Fisher's exact test, which had a significant difference (P=0.001). The testicular blood supply frequency before surgery was impaired in 19 (57.6%) cases. In control ultrasound, 15 (45.5%) testicular tissues had normal blood supply. These results were compared using Fisher's exact test, which has no significant difference (P=0.154). Conclusion: However, the sonographic changes of testicles in the patients suffering from TT were variable over time, and these changes can be widely different; they are also significantly related to testicular dimensions when the patient presents with testicular torsion.